CLIENTELISM AND THE QUALITY OF DEMOCRACY: A COMPARATIVE ANALYSIS OF RULE OF LAW AND UNIVERSALISTIC WELFARE PROVISION IN INDONESIA AND MALAYSIA - Mikail, Ahmad; Virgy, Muhammad Arief; Mustofa, Mustabsyirotul Ummah (Universitas Padjadjaran, 2026)
Clientelism remains common in Southeast Asian politics even though electoral democracy has expanded. This study examines how different forms of clientelism influence democratic quality, focusing on the rule of law and public goods provision in Indonesia and Malaysia. Building on the theories of clientelism, understood as the exchange of material benefits for political support. Such practices can weaken the fair enforcement of laws and shift public spending toward targeted groups instead of universal welfare programs. This study uses panel data from the Varieties of Democracy Institute and applies a comparative approach to analyze Indonesia and Malaysia. A multiple linear regression model is used to examine whether higher levels of clientelism are associated with weaker rule of law and lower levels of universal public-goods provision. The results show that higher levels of clientelism are linked to weaker rules of law and lower public-goods provision in both countries. However, the effects appear in different ways. In Indonesia, fragmented and candidate-centered clientelism organized through temporary broker networks is more strongly connected to the erosion of legal enforcement. In Malaysia, centralized and party-based clientelism under the United Malays National Organisation–Barisan Nasional system mainly affects the fairness and universality of welfare distribution.